POTENSI NILAI CBR TANAH TIMBUNAN DI ATAS TANAH GAMBUT DENGAN DAN TANPA PERKUATAN - Aazokhi Waruwu; Rivaldi Dojen Sitinjak; Rika Deni Susanti (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2021)
Peat soil is one type of subgrade that is not good for road construction. Peat soil has a low bearing capacity which is indicated by a low CBR value. The embankment on peat is needed to increase the CBR value, but compaction and spreading are difficult to do. Therefore, it is necessary to strengthen the combination of bamboo grids and concrete piles. The purpose of this study was to determine the potential for increasing CBR of embankment reinforced on peat soil. The research was conducted through a series of model tests in a test box filled with peat soil with and without bamboo grid reinforcement and a combination of bamboo grid and concrete piles. The CBR test was carried out on the embankment which was differentiated based on the thickness of 0-15 cm. The results showed that reinforcement can increase the CBR value of the embankment soil on peat soil. The results of the analysis for the embankment thickness of 3.93 m, the combination of bamboo grid reinforcement and concrete piles has the potential to increase the CBR value by 183% (from 5% to 14.15%) and bamboo grid reinforcement by 32% (from 5% to 6.6%).